Gibanje centralnega tezisa telesa pri metu iz skoka glede na oddaljenost od kosa - Podmenik, N.; Supej, M.; Kugovnik, O.; Erwulj, F. (Kinesiologia Slovenica, 2015)
The aim of the study was to describe, in the conditions of rest, the change in position and/or movement of the body`s centre of mass (CoM) of young male basketball players (cadets) during a jump shot from three different distances. The measurements of kinematic parameters during the shot were made using an inertial suit. The results show that the ball release occurs at different levels of the flight curve. On the shortest distances it occur 0.05s after reached maximum height in the vertical direction, on the middle distance on the peak and on largest distance 0.03 s before reaching the maximum height. The time from the beginning of the shot and take-off to the ball release shortens with an increasing distance from the basket. The time from the ball release to the landing increases with an increasing distance. In the direction towards the basket the shift increases with a longer distance until the take-off, whereas in the case of the longest distance it decreases or stops after the take-off. In the case of the longest distance, the movement of the CoM in the lateral from basket results in the largest shifts and it is statistically different from shorter distances at the beginning of the throw and at take-off (p < 0.01). From the beginning of the throw to ball release the lateral shift is 11 cm. It can be conclud ed based on the results that the movement of the CoM of young male basketball players and consequently the technique of shooting at the basket changes with distance. This is a very important finding for coaches who must be acquainted with the adjusted technique and consider this fact in the training of young basketball players.